Evaluation of the Effect of an Olive Phenolic Extract on the Secondary Shelf Life of a Fresh Pesto - Beatrice Sordini; Stefania Urbani; Sonia Esposto; Roberto Selvaggini; Luigi Daidone; Gianluca Veneziani; Maurizio Servili; Agnese Taticchi (MDPI AG, 2024)
Recent advances in the olive oil sector aim to develop sustainable strategies for the valorisation of mechanical extraction co-products as a rich source of bioactive compounds with antioxidant and antimicrobial activities. In this work, we studied the effectiveness of a phenolic extract (PE) from olive vegetation water (OVW) as a new antioxidant of natural origin for improving the quality and extending the secondary shelf life (SSL) of a fresh basil pesto sold as a served loose product at the deli counter, simulating the storage conditions after packaging, opening, and serving. For that, the PE was mixed with the oily phase of fresh pesto in two different concentrations and compared to a control pesto (CTRL) made with the addition of common additives (ascorbic acid (E300) and sorbic acid (E200)). The physicochemical parameters, phenolic and volatile composition, sensory profiles, and antioxidant capacity of the experimental pesto samples were evaluated after opening. The results proved that the enrichment with the PE improved the stability of the pesto and, hence, its overall quality. The PE provided higher protection than the CTRL against primary and secondary oxidation at both concentrations tested and delayed the accumulation of the volatile compounds responsible for the 'rancid' off-flavour up to 7 days after first opening, while also preserving higher levels of the pesto phytonutrients (such as the rosmarinic, caffeic, and chicoric acids and α-tocopherol). These results show that the generation of food waste in households, catering chains, retail, and/or restaurants can be reduced, improving the sustainability of the food industry and the competitiveness of the olive oil sector.